Flood Estimation in Al Qattara basin, southeast of Benghazi- Libya, by integrating the US Soil Conservation Service (SCS) model, geographic information systems and remote sensing techniques. - bentaher لبنى سليمان (Journal of Pure & Applied Sciences, 2022)
Estimation of water surface run-off in drainage basins significant to estimating the extent of its investment in various areas of human use. In this study, a hydromorphometric analysis was conducted for the Al Qattara Basin, located in the southeast of Benghazi-Libya, using remote sensing techniques, geographic information systems and the US Soil Conservation Service (SCS) model. The study results display that, Al Qattara Basin has an area of ​​1074.81km2 with length of 89.5km, with shape is close to a triangle, and still in the stage of maturity. The density of drainage in the basin is high due to the permeability of most of its rocks, and its streams are arranged according to the Streller method from1 to8. The concentration time in Al Qattara basin 19.55hr and response time 11.73hr indicates that low probability of flooding. The maximum water flow in Al Qattara basin is 171.6m3/sec with peak time of 13.03hr and an average surface runoff flow of 5.01m3/sec. At the end of the study, it is recommended to design a rainwater drainage network in the city to suit the annually rainfall quantities to ensure its drainage. Also, construct obstructive dams in application of the principle of rainwater harvesting. Using the integration of remote sensing and geographic information systems techniques to study the morphometric and hydrological characteristics of drainage basins in Libya to develop plans to reduce flood risks by creating an available morphometric, climatic and hydrological database.